Search for lepton-flavour-violating decays of the Higgs and Z bosons with the ATLAS detector - Çetin, Serkant Ali (SPRINGER, 2017)
Direct searches for lepton flavour violation in decays of the Higgs and Z bosons with the ATLAS detector at the LHC are presented. The following three decays are considered: H -> e tau, H -> mu tau, and Z -> mu tau. The searches are based on the data sample of proton-proton collisions collected by the ATLAS detector corresponding to an integrated luminosity of 20.3 fb(-1) at a centre-of-mass energy of root s = 8 TeV. No significant excess is observed, and upper limits on the lepton-flavour-violating branching ratios are set at the 95% confidence level: Br(H -> e tau) < 1.04%, Br(H -> mu tau) < 1.43%, and Br(Z -> mu tau) < 1.69 x 10(-5).